Toward the concert and music tourism in Solo of Indonesia - Satrya, I Dewa Gde (International Journal of Applied Sciences in Tourism and Events, 2024)
Concerts are a fun attraction. This industry is growing along with the arrival of world bands/musicians to In-donesia and performances by domestic musicians. If packaged well, concerts become a music tourism attrac-tion. This research was conducted qualitatively. Primary data was obtained through observation by attending concerts in Jakarta and Solo. Secondary data was obtained through a study of related literature. The conclu-sion of this research is that Indonesia can become a music tourism destination by holding international standard concerts on a regular basis.